Respuesta :
x + y = 5
x - y = 1
--------------add
2x = 6
x = 6/2
x = 3
x + y = 5
3 + y = 5
y = 5 - 3
y = 2
the solution is (3,2)
x - y = 1
--------------add
2x = 6
x = 6/2
x = 3
x + y = 5
3 + y = 5
y = 5 - 3
y = 2
the solution is (3,2)
x+y=5 , x-y=1
Isolate the x.
x - y (+y) = 1 (+y)
x = 1 + y
Plug in 1 + y for x in the other equation
x+y=5
(1 + y) + y = 5
1 + 2y = 5
Isolate the y. Do the opposite of PEMDAS. Note the equal sign, what you do to one side, you do to the other.
1 (-1) + 2y = 5 (-1)
2y = 4
2y/2 = 4/2
y = 2
x-y=1
Plug in 2 for y in one of the equations
x - (2) = 1
Solve for x
x - 2 (+2) = 1 (+2)
x = 1 + 2
x = 3
x = 3, y = 2
hope this helps